2005
DOI: 10.1111/j.0105-1873.2005.0654d.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to naftifine

Abstract: a case of allergic contact dermatitis due to a topical medicament containing naftifine is reporte

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…2,3 Few cases of allergic contact dermatitis owing to naftifine have been presented in the English literature. [42][43][44][45] Dermatotoxicology studies in humans showed no evidence of irritancy, phototoxicity, sensitization, or photosensitization with naftifine. 46 Crossreactivity and cross-resistance of naftifine with other allylamines have rarely been a concern with naftifine use.…”
Section: Safety Profile Of Naftifinementioning
confidence: 99%
“…2,3 Few cases of allergic contact dermatitis owing to naftifine have been presented in the English literature. [42][43][44][45] Dermatotoxicology studies in humans showed no evidence of irritancy, phototoxicity, sensitization, or photosensitization with naftifine. 46 Crossreactivity and cross-resistance of naftifine with other allylamines have rarely been a concern with naftifine use.…”
Section: Safety Profile Of Naftifinementioning
confidence: 99%